Increasing Community Income Through Tilapia Farming In Bontomatene Village, Pangkep - Mariam, Mariam; Walinono, Andi Rusdi; Karma, Karma; Ahmad, Ilham; Purnamasari, Lilis (Yayasan Cendekiawan Digital Indonesia, 2024)
The purpose of the Community Partnership Program activities is Fisheries Development in Rumah Great Village. The method used in the implementation of the program is carried out through three stages. In the first stage, fish farming to farmer groups. The next stage is to provide assistance with fish pellet molding machines and materials for making fish pellets. Then, guiding the fish farmer group in using the pellet molding machine and making tilapia pellets directly by mixing various types of fish pellet-making materials according to the dosage. In the last stage, the service team handed over 4000 tilapia seeds to be stocked in the pond that became the activity area, so that the farmer group could start cultivation activities with the help of tilapia seeds. Based on the results of interviews with the community, especially farmer groups on community service activities carried out by the service team, they feel that this activity has increased knowledge about tilapia farming, this activity also improves the skills of farmer groups in making tilapia pellet feed using a pellet molding machine.